The mother-child papers - Ostriker, Alicia (Pitt poetry series., 2009)
In 1970, as the war in Vietnam was heating up, Ostriker was awaiting the birth of her son. On April 30, President Nixon announced the bombing of Cambodia. On May 14, four students were shot and killed by National Guardsmen at Kent State University. The poems in this collection confront Ostriker's personal tumult as she considered the world she had brought her son into.